Authoritarian Parenting Practices on Korean Drama: Reception Analysis on SKY Castle - Setianoto, Fiona Angeline; Primadini, Intan (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
The Korean drama "SKY Castle" received the highest rating of any Korean drama, coming in at 23.78%. The drama "SKY Castle" explores authoritarian parenting and rivalry in South Korean schooling, according to director Jo Hyun Tak. SKY Castle addresses social concerns that are grounded in South Korean reality and bear similarities to social realities in Indonesia. One type of authoritarian parenting that parents in Indonesia engage in is forcing their children to choose their college and university majors. This is because parents have preconceived notions about certain majors and public universities, believing that it will ensure their children's success and financial security. The Stuart Hall reception analysis method is applied in this qualitative study. Interviews and document reviews are the data-collecting methods used in this study. Based on their cultural experiences and backgrounds, the results demonstrate that every informant's viewpoint on authoritarian parenting in the Korean drama "SKY Castle" varies. Mostly because parents of the informants have preconceived notions about certain majors, particularly STEM majors like engineering, medicine, law, and public universities, which can negatively affect both the parent-child bond and the mental health of the child. The informants concurred that SKY Castle depicts parents in an authoritarian manner; nonetheless, majority of them brought up Professor Cha's family, pointing out that other families do not treat their kids harshly. The five informants are, in summary, in a negotiated position.